SURGICAL MANAGEMENT OF UNERUPTED CANINES: A CASE REPORT - dhir, shikha; Polepalle, Tejaswin; Patel, Lipsa; Dave, Dhwani (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Management of impacted canines includes an interdisciplinary approach to achieve desired esthetics, and functional, and occlusal treatment goals. The present case series included various surgical procedures, used for the management of impacted canines and it also highlights the periodontal and orthodontic considerations to be taken before surgical canine exposure. The surgical exposure of canine creates a sufficient space and view of teeth that helps in the proper orthodontic extrusion and traction of teeth into the dental arch.